Dopuszczalność stosowania przepisów o wzorcach udostępnianych w systemie teleinformatycznym do EIZG z siedzibą na terytorium Rzeczypospolitej Polskiej - Kozieł, Grzegorz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The study concerns the legal issue of the admissibility of applying the provisions on templates provided in the ICT system to the European Economic Interest Grouping located on the territory of the Republic of Poland. The existing law does not directly provide such a possibility. However, due to the fact that art. 7 of the Act on EEIG and SE, provides appropriate application, in matters not regulated in Regulation No. 2137/85 / EEC and the Act on EEIG and SE, the provisions of Code of Commercial Partnerships and Companies on a general partnership, the study considered: 1) whether this could also refer to the provisions on the listed templates provided for the general partnership (and therefore whether they can be applied respectively to the EEIG located in the territory of the Republic of Poland), what arguments are in favor of this application, and, 2) what is the significance, in this area, of the existence of implementing regulations specifying such templates and 3) whether there is a statutory delegation in the legal system to issue these provisions, as in the case of templates in a general partnership.